Peningkatan Kualitas Program Studi Pendidikan Bahasa Inggris Jurusan Tarbiyah Sekolah Tinggi Agama Islam Negeri (STAIN) Samarinda Berbasis Akreditasi - Dina Destari (FENOMENA, 2015)
The objective of this study was to know the strategy of English department program management to improve the quality its program through acreditation standard. The data were collected by using observation, interview, and documentation. Data were analyzed by using SWOT analysis. Improving the quality of English department consists of: 1) developing the vision, mission, and the target of the English study program, 2) strengthening the management and quality assurance of the English program, 3) improving the quality of the alumni of English study program, 4) improving the human resources of the English study program, 5) evaluating curriculum and management of the English study program, 6) developing the fund, facilities, and information system of the English study program, and 7) networking and developing the research, community services, and cooperration with other parties.